Wajah Multikulturalisme Eropa: Ancaman atas Kehidupan Sosial Politik Imigran Muslim di Inggris - Siswanto Siswanto (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2012)
This article describe Europe multiculturalism especially Muslim social life in England. One of important social issues in the country is unharmony relation between British society and Muslim imigrant. This is an irony because European community eventually is based on liberalism which give freedom to citizen and non-discrimination principle. There are few condition which cause discrimination in UK, as follow; social jealous to imigrant in Europe as we known that many immigrant who success in its business or working and there is opinion that immigrant take over job opportunity from indigenous people in Europe and misperception to Islam.Keyword: Europe, multiculturalism, immigrant, Muslim